Occupational cancer in Britain: Statistical methodology - Hutchings, Sally J (Nature Publishing Group, 2012)
An approach using the attributable fraction (AF) has been developed to estimate the current burden of occupational cancer in Britain. The AF combines the relative risk (RR) associated with exposure with the proportion exposed. For each cancer–exposure pairing, the RR is selected from key epidemiological literature such as an industry, or population-based study, meta-analysis or review. The CARcinogen EXposure (CAREX) database provides point estimates for the number of workers exposed to a range of carcinogens; alternative sources are national surveys such as the Labour Force Survey and Census of Employment. The number of workers exposed are split between high and low exposure levels matched to appropriate RRs from the literature. The relevant period for cancer development during which exposure occurred is defined as the risk exposure period (REP). Estimation of the numbers ever exposed over the REP takes into account the changes in the number of people employed in primary and manufacturing industry and service sectors in Britain where appropriate, and adjustment is made for staff turnover over the period and for life expectancy. National estimates of the population ever of working age during the REP are used for the proportion denominator. Strategies have been developed to combine exposure AFs correctly while avoiding double counting and minimising bias. The AFs are applied to national cancer deaths and registrations to obtain occupation-attributable cancer numbers. The methods are adaptable for other diseases and other geographies, and are also adaptable to more sophisticated modelling if better exposure and dose–response data are available.